2021
DOI: 10.3389/fphar.2021.784909
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation of G6PD and CYP2D6: Clinical Implications on the Use of Primaquine for Elimination of Plasmodium vivax

Abstract: Primaquine, an 8-aminoquinoline, is the only medication approved by the World Health Organization to treat the hypnozoite stage of Plasmodium vivax and P. ovale malaria. Relapse, triggered by activation of dormant hypnozoites in the liver, can occur weeks to years after primary infection, and provides the predominant source of transmission in endemic settings. Hence, primaquine is essential for individual treatment and P. vivax elimination efforts. However, primaquine use is limited by the risk of life-threate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 72 publications
(94 reference statements)
0
8
0
Order By: Relevance
“…Both G6PD and CYP2D6 are highly polymorphic genes, which makes the use of primaquine more complex (34). In studies that evaluated the pharmacokinetics of PQ with CYP2D6 metabolizers, it was observed that the drug concentration was higher in gPM, and that the low production of active metabolites was responsible for its effectiveness, which would result in relapse and failure (14).…”
Section: Discussionmentioning
confidence: 99%
“…Both G6PD and CYP2D6 are highly polymorphic genes, which makes the use of primaquine more complex (34). In studies that evaluated the pharmacokinetics of PQ with CYP2D6 metabolizers, it was observed that the drug concentration was higher in gPM, and that the low production of active metabolites was responsible for its effectiveness, which would result in relapse and failure (14).…”
Section: Discussionmentioning
confidence: 99%
“…Resulting predictions of activity indicate that the use of PQ following current protocols may be more effective in some malaria-endemic regions than in others as a result of high frequencies of poor metabolizer alleles in East Asia. Stewart et al have called further attention to similar populationspecific concerns in Central America as summarized previously (Stewart et al, 2021).…”
Section: Pharmacogenomics and Cyp2d6 Phenotypementioning
confidence: 99%
“…This is consistent with recent clinical trials to test optimal dosing strategies against relapse infections ( Brito-Sousa et al, 2022 ; Chamma-Siqueira et al, 2022 ). An adjoining article by Stewart et al focuses on implications of CYP2D6 and G6PD genetic variation on potential treatment approaches and limitations for P. vivax as well as P. ovale (that also produces hypnozoites) liver stage parasites ( Stewart et al, 2021 ).…”
Section: Introduction—malaria Primaquine and Human Geneticsmentioning
confidence: 99%
“…As a final test, they monitored participants’ sera for satisfactory clearance of PQ over 24 hours after administration of a test dose. These parameters are also of major relevance to the field as it is estimated that the combination of G6PDH deficiency and reduced functioning CYP2D6 account for nearly 40% of the population at risk of P. vivax infection ineligible for PQ therapy ( 50 ). For blood-stage CHMI in which hypnozoite formation does not occur, screening for G6PD and CYP2D6 can be omitted, as PQ treatment is not indicated.…”
Section: Healthy Volunteer Inclusion/exclusion Criteriamentioning
confidence: 99%